The Cool Circumgalactic Medium of Low-redshift Star-forming Galaxies. I. Empirical Model and Mean Properties - Yakov Faerman; Jessica K. Werk (The Astrophysical Journal, 2023)
We present an analytic model for the cool, T ∼ 10 ^4 K, circumgalactic medium (CGM), describing the gas distribution, and thermal and ionization states. Our model assumes (total) pressure equilibrium with the ambient warm/hot CGM, photoionization by the metagalactic radiation, and allows for nonthermal pressure support, parameterized by the ratio of thermal pressures, η = P _hot,th / P _cool,th . We apply the model to the COS-Halos measurements and find that a nominal model with η = 3, gas distribution out to r ≈ 0.6 R _vir , and M _cool = 3 × 10 ^9 M _⊙ , corresponding to a volume filling fraction of f _V,cool ≈ 1%, reproduces the H i and low/intermediate metal ions (C ii , C iii , Si ii , Si iii , and Mg ii ) mean column densities. Variation of ±0.5 dex in η or M _cool encompasses ∼2/3 of the scatter between objects. Our nominal model underproduces the measured C iv and Si iv columns, and these can be reproduced with (i) a cool phase with M _cool ∼ 10 ^10 M _⊙ and η ≈ 5, or (ii) cooling or mixing gas at intermediate temperatures, with M ∼ 1.5 × 10 ^10 M _⊙ and occupying ∼1/2 of the total CGM volume. For cool gas with f _V,cool ≈ 1%, we estimate an upper limit on the cloud sizes, R _cl ≲ 0.5 kpc. Our results suggest that for the average galaxy CGM, the mass and nonthermal support in the cool phase are lower than previously estimated, and extreme scenarios are not necessary. We estimate the rates of cool gas depletion and replenishment, and find accretion onto the galaxy can be offset, allowing ${\dot{M}}_{cool}≈ 0$ over long timescales.